Analisis Price Discount Dan Bonus Pack Sebagai Strategi Penjualan Dan Pengaruhnya Terhadap Minat Beli Konsumen “Retail Indomaret” Sibuhuan - Lubis, Paija; Othman, Lie (Peneliti.net, 2026)
This study aims to analyze the influence of price discount and bonus pack on consumer purchase intention at Indomaret retail in Sibuhuan. The method used is descriptive quantitative, with primary data obtained through questionnaires and secondary data from relevant literature. The sampling technique used is non-probability sampling with a purposive sampling approach, by selecting respondents who have made purchases at Indomaret Sibuhuan. Data analysis was conducted using SPSS, including validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity), simple and multiple linear regression, coefficient of determination (R²), as well as t-test and F-test. The results show that price discount and bonus pack have a significant effect, both partially and simultaneously, on consumer purchase intention retail Indomaret Sibuhuan.